1999
DOI: 10.1203/00006450-199910000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Preterm Infants after Hospital Discharge: Effect of Diet on Body Composition

Abstract: Our purpose in this study was to examine whole body composition, using dual energy x-ray absorptiometry (DEXA) during dietary intervention in preterm infants (< or = 1750 g birthweight, < or = 34 wk gestation). At discharge, infants were randomized to be fed either a preterm infant formula (discharge-6 mo; group A) or a term formula (discharge-6 mo; group B), or the preterm formula (discharge-term) and the term formula (term-6 mo; group C). Nutrient intake was measured between each clinic visit. To measure bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 8 publications
3
65
1
4
Order By: Relevance
“…Improvements in growth and lean body mass appeared to be related to differences in protein intake, further supporting the idea that inadequate protein intake is a common problem in these high-risk infants (5,6).…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Improvements in growth and lean body mass appeared to be related to differences in protein intake, further supporting the idea that inadequate protein intake is a common problem in these high-risk infants (5,6).…”
supporting
confidence: 51%
“…In our previous studies, we demonstrated that a formula containing 2.2 g protein and 80 kcal/100 mL improved growth when compared with a formula containing 1.4 g protein and 66 kcal/100 mL (5,6). Improved growth appeared to be due to increased protein intake as caloric intakes were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Post-natally, pre-term infant boys grow faster and accrete more lean mass than pre-term girls (21). Pre-term boys fed a protein-enriched formula also grow faster and accrete more lean mass than girls fed the same formula (22). If boys are programmed to grow faster and intake better met requirements then gain would also tend to be greater.…”
Section: Protein-energy Needs Of Pre-term Infantsmentioning
confidence: 99%
“…Body composition measurements made using dual X-ray absorptiometry (DXA) suggested that the additional weight gain was composed predominantly of lean tissue rather than fat. 19 There were no significant differences in neurodevelopment measured using the Bayley Scales of Infant Development at 18 months.…”
Section: Introductionmentioning
confidence: 99%